Evaluation of Interaction Design of Virtual Laboratory of Open Source Programming in Virtual Classroom Based On Moodle Using DECIDE Framework Case Study: C programming - Zakiah, Azizah (International Journal of Psychosocial Rehabilitation, 2020)
Identifying usability and user experience goals is essential for making every product successful, and this requires understanding users’ needs. The role of evaluation is to make sure that this understanding occurs during all the stages of the product’s development. with evaluation playing a key role in facilitating understanding between designers and users. In this research, focus on an evaluation interaction design of a virtual laboratory of open source programming in a virtual classroom based in Moodle using the DECIDE framework. The approach and method are usability tests. The results of the questionnaire are presented in tables. The testing result showed that respondents agree that the virtual laboratory is in accordance with the goals of usability and user experience that is effective, efficient, safe to use, good utility, easy to learn, and easy to remember by users. Respondents also agree that the virtual laboratory will support them to get the objectives of learning of C programming